Atributos de valor da atratividade em institui????es de ensino superior privadas brasileiras - Vivan, Antonio Marcos (2016)
The attractiveness of Higher Education Institutes (HEIs), especially private HEIs, has been infrequently referenced in bibliographical studies from 1926 to 2015. In fact, this study searched in the bibliography of the main bases of international publications, and found the nonexistence of research that binds attribute value to institutional attractiveness. Therefore, this work focuses on the relationship between the attributes of value and the tangible and intangible aspects for the construction of the attractiveness of private HEIs in Brazil. This was completed by validating a theoretical model, submitted to educational managers. 2376 private Brazilian HEIs, and non-profits, registered in MEC (Ministry of Education and Culture), were contacted, which resulted in obtaining 108 validated questionnaires responses. We tested two research models using multivariate analysis and modeling of structural equations. One of them, defined as linear, advocates a positive and significant relationship between tangible and intangible attributes, in that order, and considers the tangible attributes are responsible for these intangible attributes and the construction of institutional attractiveness. The other model, called competitor, considers that the tangible and intangible attributes are autonomous and simultaneously build the institutional attractiveness. The main results indicate that both the linear model and the competitor were validated. The linear model explained 64% of the existing variance in the dependent variable (attractiveness). The competing model, however, explained 81% of variance and after convergent and discriminant validity, this same model still had the ability to explain 79% of the variance observed in the dependent variable. The results also indicate that, among the 34 attributes of value surveyed, some stood out as the other grounds of possible strategies of attractiveness. It can be concluded that first, institutional attractiveness is built through attributes of tangible and intangible value. Second, the competing model of construction of attractiveness is more robust than the linear model for the explanation as the most effective format for construction of institutional attractiveness. Third, depending on the momentum of HEI it is possible to determine the best combination of routes of the attributes of value; so that it can build strategies that increase its institutional attractiveness. Finally, the models open a new frontier in the knowledge of the management of IES, for the expansion of knowledge and methodologies of institutional management of Higher Education Institutions.